Students’ Transition from Secondary School French Programs into University Level French Immersion - Séror, Jérémie; Weinberg, Alysse (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2021)
A great deal of time and resources are invested throughout Canada to encourage students to learn French as a second official language through a variety of programs (core French, intensive French, and French immersion programs). Little is known, however, about the impact of these efforts once French language learners complete their high school studies. This paper reports on longitudinal qualitative case studies of two students registered within a Canadian university-level immersion stream. Drawing on an academic discourse socialization approach, the paper examines students’ perspectives of their literacy development as they transition from high school French language programs to a universitylevel immersion program designed to promote advanced levels of bilingualism. Findings stress how the experience of transitioning from French high school programs to university immersion challenges students’ perception of themselves as French learners and their notion of the legitimacy of their high school French experiences.